Pengaruh Employee Stock Ownership Program, Total Asset Turnover dan Leverage Terhadap Return On Asset pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Rosalina Yessyca; Wadhan (IAIN Madura, 2021)
This research uses a quantitative approach with associative type and uses multiple linear regression analysis method. The data source is obtained from secondary data in the form of annual financial reports obtained through the official website of the Indonesia Stock Exchange with a sample of 10 companies and using four reporting periods. The results of this study indicate that the results of calculations and statistical tests with linear regression method using SPSS produce an R square value of 0.504 or 50.4%, this indicates that simultaneously the independent variables (ESOP, TATO, Leverage) have an effect of 50.4% on dependent variable (ROA) and the rest is influenced by other factors not examined. And based on partial testing, each independent variable (ESOP, TATO, Leverage) has a significant effect on the dependent variable (ROA) seen from the t-count value (3.321; 3.874; 2.813) which is greater than the t table (2.030).